2011
DOI: 10.1097/brs.0b013e3181d449ec
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of Pedicle Screws in Osteoporotic Bone With Bioactive Cement Augmentation Using Simulated In Vivo Multicomponent Loading

Abstract: We believe our test protocol produced screw loosening failure similar to that observed clinically, and that it has the ability to detect differences in failure initiation force and failure modes to compare short-term efficacy of screw augmentation techniques. All cements improved screw resistance to failure. The CP > CS > M failure initiation force (P < 0.006) was because of differences in cement distribution. Animal studies may be required to characterize the remodeling activity of bioactive cements and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 19 publications
1
41
0
Order By: Relevance
“…Burval et al [46] showed increased pedicle screw pullout loads in osteoporotic human cadavers with transpedicular polymethyl methacrylate screw augmentation. Choma et al [47] used cement augmentation in a biomechanical model designed to simulate pullout, transverse, and moment loading; all cement types used (calcium phosphate, calcium sulfate, and proprietary mixture) provided additional screw resistance in synthetic osteoporotic bone. Application of cement augmentation techniques in patients with poor bone quality due to tumor or osteoporosis has also been successful.…”
Section: Discussionmentioning
confidence: 99%
“…Burval et al [46] showed increased pedicle screw pullout loads in osteoporotic human cadavers with transpedicular polymethyl methacrylate screw augmentation. Choma et al [47] used cement augmentation in a biomechanical model designed to simulate pullout, transverse, and moment loading; all cement types used (calcium phosphate, calcium sulfate, and proprietary mixture) provided additional screw resistance in synthetic osteoporotic bone. Application of cement augmentation techniques in patients with poor bone quality due to tumor or osteoporosis has also been successful.…”
Section: Discussionmentioning
confidence: 99%
“…Choma et al [11] developed a foam model, which allowed a combination of axial pullout and flexion bending moment, having unconstrained screw motion within the foam. They hypothesized that pedicle screw loosening was further due to compressive loads resulting in viscoelastic creep of demineralized cancellous bone.…”
Section: Discussionmentioning
confidence: 99%
“…It may be the more clinically relevant loading that the instrumentation must withstand. This can result in progressive toggle migration in the elderly spine and finally lead to screw pullout [11,12]. It would therefore be interesting to set up an experiment, which allows several stress components rather than axial pullout of the screw.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is increasing debate over its clinical relevance for pedicle screw testing, especially since pullout has rarely been reported clinically as a failure mechanism (reported rates of 0-1.3 %) [13][14][15]. Furthermore, fatigue failure of the bone under cyclic toggling loading is believed to be more clinically relevant [10,11,16].…”
Section: Introductionmentioning
confidence: 98%